Plusaetis sibynus (Siphonaptera: Ceratophyllidae): a new record of flea on Didelphis virginiana, with a checklist of fleas for this host - Glebskiy, Yury; Acosta-Gutiérrez, Roxana; Cano-Santana, Zenón (Therya Notes, 2021)
Virginia opossums (Didelphis virginiana) are hosts to a variety of fleas that can be important vectors for diseases, including some zoonosis; therefore, it is important to generate knowledge about the fleas that parasite this animal. We present the list of all fleas found on opossums, and the discovery of a species that has not been previously found on D. virginiana, neither on other marsupials. We collected fleas from Virginia opossums in the urban area of México City, México, and performed a bibliographical search to determine which species of fleas were previously recorded. We found previous records of 26 species of fleas on opossums, and we added the flea species Plusaetis sibynus to this list. Plusaetis sibynus is a common flea of rodents (mainly Peromyscus and Neotoma), representing a potential vector of diseases from these rodents to the opossum and human populations. Further research is needed to assess the role of this flea as a vector of zoonotic diseases.